PHARMACOGNOSTIC AND PHYSICOCHEMICAL EVALUATION OF SOLANUM VIRGINIANUM L LEAVES (SOLANACEAE) - S. SUNDAR; Y. JUSTIN KOIL PILLAI (International Journal of Pharma and Bio Sciences, 2016)
The whole plant of Solanum virginianum L is reported to have great medicinal value. It is found effectively treating worms, cold, fever, hepatomegaly, muscular pain, urinary stones, etc. Nasal administration is beneficial in migraine, asthma and headache. The present investigation was therefore undertaken to evaluate the requisite pharmacognostical standards by studying macroscopic and microscopic characters for the leaf material of Solanum virginianum L. The physicochemical properties such as loss on drying (5.6%), total ash value (13.54%), acid insoluble ash value (4.25%), water soluble ash value (12.35%), alcohol soluble extractive value (8.5%), water soluble extractive value (23%) and petroleum ether soluble extractive value (4.2%) were carried out. The fluorescent analysis was carried out by using different chemicals. These studies provided crucial information for the correct identification and standardization of this leaf material. Further studies could also be carried out to characterize and screen the valuable compounds present in the leaves of this plant.